Synthesis and characterization of Cp*Ir-dithiolene-o-carborane phosphine complexes: A continuous investigation of B−H⋯π interaction. (18th June 2019) - Cao, Hou-ji; Dai, Huimin; Zhang, Xiaolei; Yan, Hong; Lu, Changsheng
ABSTRACT: B−H⋯π interaction has attracted increasing attention after its experimental and theoretical verifications in [ Cp ∗ Ir(PR3 )(S2 C2 B10 H10 )] (R = C6 H4 X, X = H, F, OMe) complexes. In such a template, the entropic factors are excluded by using triphenylphosphines as sterically crowding ligands, which leads to the direct observation of B−H⋯π hydrogen bonds at room temperature in both solution and solid state. In this work, new Cp ∗ Ir − dithiolene- o -carborane templates with sterically less crowding mono/diphenylphosphine ligands were designed and experimentally synthesised. As a result, non-covalent B−H⋯π hydrogen bonds were detected at low temperatures (down to −80°C) inC1 by using low temperature NMR techniques. Furthermore, variable temperature NMR measurement ofC0 with triphenylphosphine ligation was also performed which indicates the slow rotation of Ir−P bond and the reinforced B−H⋯π interaction at low temperature. These experimental results are consistent with the previous theoretical prediction of the B−H⋯π interaction at low temperature in the B2 H6 ⋯benzene model. Additionally, if monophosphine ligand is replaced by diphosphine, a new type of intermolecular B−H⋯π interaction has been crystallographically observed in solid state. GRAPHICAL ABSTRACT: